Evaluation of used eye drop containers for microbial contamination in outpatient department of tertiary care teaching hospital - P. Bachewar, Narendra; Deshmukh, Durgesh; Choudhari, Sachin R.; Joshi, R. S. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Contaminated eyedrops are considered as serious risk factor for many iatrogenic ocular infections. Apart from the risk of infection, microbial contamination may alter the pH of the solution thereby reducing the efficacy of drugs. Presently many preservatives are added to these eye drops preparations to extend the duration of use. Hence authors aimed this study to find the contamination rates in such eye drop preparations. Methods: This was a prospective observational research conducted at Ophthalmology OPD, of tertiary care teaching hospital for the period of 2 months. Total fifty five used eyedrops were collected. Results: Authors found that 25.45% of the collected eye drops were contaminated with various organisms, viz. E. coli (10.90%), Staphylococcus aureus (9.09%), Pseudomonas aerugenosa (1.81%), Bacillus subtilis (1.81%) and Candida albicans (1.81%). Among various eyedrops, mydriatic (60%) eyedrops had the highest rate of contamination. We also found that, different preservatives in the eye drops were presents with different level of microbial contamination. Conclusions: The present study showed that there is a definite co-occurrence between eyedrop contamination and ocular infections irrespective of preservatives. This research raises a concern about questionable efficacy of preservatives.